Model of emission of exhaust compounds of jet aircraft in cruise phase enabling trajectory optimization - Pawlak, Małgorzata; Majka, Andrzej; Kuzniar, Michal; Pawluczy, Jowita (Transport, 2020)
Nowadays, air transport is the most modern and the most dynamically developing branch of transport. This intensive development of air transport causes the continuous increase in emissions of pollutants, mainly greenhouse gases, leading to the deepening of the greenhouse effect, which in turn leads to irreversible global climate change. In order to optimize air communication and make it even more economical and environmentally friendly, such activities as e.g. SESAR project are undertaken. One of the parts of this project is the research on minimizing fuel consumption and emissions of pollutants in jet engine exhausts. The paper presents a developed model of emission and main pollutants (NOx, CO, HC and CO2) in the exhausts of jet engines of a passenger aircraft during a cruise phase. Applying simple optimization tools, such as e.g. the Dijkstra’s algorithm, this model was verified by the optimization of a trajectory of a jet aircraft in a cruise phase on an exemplary route in terms of minimizing emission of selected harmful compounds in jet engines exhausts. To meet the aim of the research, it was necessary to develop a computer program that determines a two-dimensional grid graph, assigns its appropriate weights to its edges and passing along these edges, determines the optimal trajectory of a given flight between two indicated start and end vertices. The developed research methodology is universal and can be applied for any jet passenger aircraft.